Effect of Annealing Temperature and Dopant Concentration on the Surface Layer of Indium Doped Ba0.5Sr0.5TiO3 Thin Film - Noor Khairul Anuar Johari (Universiti Malaysia Perlis, 2008)
Access is limited to UniMAP community.